ANTIBACTERIAL ACTIVITY OF RAMANIA LEAF EXTRACT (Bouea Macrophylla Griff) AGAINST THE GROWTH Actinomyces spp - Nor Laila Hayati; Isyana Erlita; Juli Harnida Purwaningayu (Dentino : Jurnal Kedokteran Gigi, 2023)
ABSTRACTBackground: One of the causes of tooth nerve death or pulp necrosis is microorganisms, namely is Actinomyces spp. Ramania leaf extract (Bouea Macrophylla Griff) contains secondary metabolites, namely triterpenoids, alkaloids, saponins, tannins, flavonoids, steroids, and phenolics which function to inhibit the growth of Actinomyces spp. Purpose: This study aims to analyze the antibacterial activity of ramania leaf extract (Bouea Macrophylla Griff) at concentrations of 6,25%, 12,5%, 25%, 50%, and 100% against the growth Actinomyces spp. Methods: This research is a pure experimental (true experimental), with Posttest Only with Control Group Design. Antibacterial activity test used a paper disc diffusion with seven treatments, namely ramania leaf extract (Bouea Macrophylla Griff) with a concentration of 6,25%, 12,5%, 25%, 50%, and 100%, Chlorhexidine gluconate 2% as a positive control and Aquades as a negative control of Actinomyces spp were repeated 5 times. Measuring the diameter of the clear zone formed on Mueller Hinton Agar (MHA) media using a caliper. Results: Based on the results of the Mann Whitney test, there was 1 pair of groups that did not differ significantly in inhibiting Actinomyces spp bacteria, namely the 25% concentration group with a positive control of 2% Chlorhexidine gluconate, while the other groups had significant differences from each other. Conclusion: There is antibacterial activity in ramania leaf extract (Bouea Macrophylla Griff) against Actinomyces spp. Keywords: Actinomyces spp, Antibacterial Activities, Chlorhexidine gluconate 2%, Ramania Leaf Extract.